Quantitative proteomics analysis of BMS‐214662 effects on CD34 positive cells from chronic myeloid leukaemia patients. Issue 1 (11th January 2013) - Balabanov, Stefan; Evans, Caroline A.; Abraham, Sheela A.; Pellicano, Francesca; Copland, Mhairi; Walker, Michael J.; Whetton, Anthony D.; Holyoake, Tessa L.
<x xml:space="preserve">Abstract</x> Chronic myeloid leukaemia (CML) arises in a haemopoietic stem cell and is driven by the Bcr‐Abl oncoprotein. Abl kinase inhibitors (protein tyrosine kinase inhibitors) represent standard treatment for CML and induce remission in the majority of patients with early disease, however these drugs do not target leukaemic stem cells (LSCs) effectively, thus preventing cure. Previously, we identified the farnesyl transferase inhibitor BMS‐214662 as a selective inducer of apoptosis in LSCs of CML patients relative to normal controls; however, the mechanism underlying LSC‐specific apoptosis remains unclear. To identify pathways involved in the favourable effects of BMS‐214662 in CML, we employed a proteomic approach (based on iTRAQ) to analyse changes in protein expression in response to drug treatment in the nuclear and cytoplasmic fractions of CD34+ CML cells. The study identified 88 proteins as altered after drug treatment, which included proteins known to be involved in nucleic acid metabolism, oncogenesis, developmental processes and intracellular protein trafficking. We found that expression of Ebp1, a negative regulator of proliferation, was upregulated in the nucleus of BMS‐214662‐treated cells. Furthermore, proteins showing altered levels in the cytosol, such as histones, were predominantly derived from the nucleus and BMS‐214662 affected expression levels of nuclear pore complex proteins. Validation of key facets of these observations suggests that drug‐induced alterations in protein localisation, potentially via loss of nuclear membrane integrity, contributes to the LSC specificity of BMS‐214662, possibly via Ran proteins as targets.